Design and Research of the Energy Supplement System for Ocean Buoys - Fang Zifan; Zhang Liming; Zhao Shuang; Zuo Xinqiu (Jixie chuandong)
Aiming at the problem of energy supplement for ocean buoys, an energy supplement system for ocean buoys is designed. The buoy shakes under the action of waves. The energy supplement system located inside the buoy collects the kinetic energy of shaking and converts it into stable electric energy for the buoy to recharge or store electricity; the working principle, design scheme and structural composition of the energy supplement system of the marine buoy are determined; according to the motion principle of the sloshing pendulum, the torque equation of the sloshing pendulum is established; AQWA is used to simulate the motion characteristics of the float under the action of first-order regular and irregular waves, and the roll angular displacement of the float is taken as the input of the simulation model. The electromechanical coupling simulation model of the system is built by using the joint simulation of Adams and AMESim, which verifies the rationality of the design scheme. The results show that under the action of first-order regular wave and irregular wave, the energy supplement system can generate 3.3 V and 1 A DC power to realize stable power output and recharge the buoy or battery.